Co-occurrence of Wilson's disease and Duchenne muscular dystrophy in a Chinese patient: a case report - Wang, Jiawei; Sun, Dandan; Wang, Yu; Fang, Mingjuan; Wang, Xun (Frontiers in Pediatrics, 2025)
Wilson's disease (WD) and Duchenne muscular dystrophy (DMD) are rare genetic diseases, and their co-occurrence is even rarer. Here, we describe our experience diagnosing a 6-year-old male Chinese patient presenting with an atypical phenotype and two genetic causative factors who was ultimately diagnosed with coexisting WD and DMD. We used a comprehensive and systematic evaluation of the patient's history, physical examinations, laboratory tests, and genetic testing to make the diagnosis. The patient was treated for one year with therapy to inhibit copper absorption and an anti-inflammatory treatment, and their condition remained stable. This case suggests that the inflammatory response could be a common pathogenesis between these two diseases. It also demonstrates the clinical efficacy of anti-inflammatory therapy for WD with DMD. Furthermore, this case illustrates the importance of taking a detailed history and performing thorough physical examinations to diagnose coexisting hereditary diseases.